In vitro assessment of proportional assist ventilation. Issue 5 (7th June 2010) - Patel, Deena-Shefali; Rafferty, Gerrard F; Hannam, Simon; Lee, Silke; Milner, Anthony D; Greenough, Anne
Abstract : Objective: During proportional assist ventilation (PAV) the timing and frequency of inflations are controlled by the patient and the patient's work of breathing may be relieved by elastic and/or resistive unloading. It is important and the authors' objective to determine whether ventilators delivering PAV function well in situations mimicking neonatal respiratory conditions. Design: In vitro laboratory study. Setting: Tertiary neonatal ICU. Interventions: Dynamic lung models were developed which mimicked respiratory distress syndrome, bronchopulmonary dysplasia and meconium aspiration syndrome to assess the performance of the Stephanie® neonatal ventilator. Main outcome measures: The effects of elastic and resistive unloading on inflation pressures and airway pressure wave forms and whether increasing unloading was matched by an 'inspiratory' load reduction. Results: During unloading, delivered pressures were between 1 and 4 cm H2 O above those expected. Oscillations appeared in the airway pressure wave form when the elastic unloading was greater than 0.5 cm H2 O/ml with a low resistance model and 1.5 cm H2 O/ml with a high resistance model and when the resistive unloading was greater than 100 cm H2 O/l/s. There was a time lag in the delivery of airway pressure of at least 60 ms, but increasing unloading was matched by an inspiratory load reduction. Conclusions: During PAV, unloading does reduce inspiratory load, but there are wave form abnormalities and a time lag in delivery of the inflation pressure. The impact of these problems needs careful evaluation in the clinical setting.